Gender-related variation in the clinical presentation and outcomes of critical limb ischemia - McCoach, Caroline E (2013)
Critical limb ischemia (CLI) is a major cause of limb loss and mortality among patients with advanced peripheral artery disease. Our objective was to evaluate the gender-specific differences in patient characteristics and clinical outcomes among patients with CLI. We performed a retrospective analysis of 97 women and 122 men presenting with CLI who underwent angiography from 2006 to 2010. Baseline demographics, procedural details, and lesion characteristics were assessed for each patient. Kaplan–Meier analysis was used to assess long-term patient and lesion-level outcomes. Cox proportional hazard modeling was used to evaluate the relationship between gender and major adverse cardiovascular events (MACE). Compared to men, women were less likely to have a history of coronary artery disease (39% vs 54%, p = 0.02) or diabetes (57% vs 70%, p = 0.05) but had similar baseline medical therapy. At angiography, women were more likely to have significant femoropopliteal (77% vs 67%, p = 0.02) and multi-level infrainguinal disease (63% vs 51%, p = 0.02). Women were also more likely to undergo multi-vessel percutaneous intervention (69% vs 55%, p = 0.05), but had similar rates of limb salvage after percutaneous intervention or surgical bypass (HR 0.94 [95% CI 0.45–1.94], p = 0.9). During follow-up, women had higher rates of subsequent major adverse cardiovascular events (HR 1.63 [95% CI 1.01–2.63], p = 0.04). In conclusion, women with CLI are more likely to present with femoropopliteal and multi-level infrainguinal disease. Despite similar rates of limb salvage, women with CLI have an increased rate of subsequent major adverse cardiovascular events.